Podmioty postępowania sądowoadministracyjnego - Kułak-Krzysiak, Katarzyna (Przegląd Prawno-Ekonomiczny, 2008)
Streszcznie dostępne wyłącznie w języku angielskim: The term ‘a party’ in the context of art.12, combines three kinds of bodies in administrative procedure. It includs a claimant and a defendant of administrative procedure and also a third party involved or according to the letter of statute‘a participant’. Therefore, at every instance the statute mentions that the claimant or defendant is entitled to a right, other participants are also entitled to it. A claim is decided by an independent administrative court. There are, however, two types of party entitled to bring a claim: these who are bringing a claim in their own interest and those acting on behalf of others in order to protect the rule of law. There are therefore two acting parites of contradicting interests. In the above article my aim was to briefly describe the term and meaning of ‚a party’ in judicial-administrative procedure.